Association between COVID-19 Vaccine and New-Onset Atrial Fibrillation - Ajmera, Kunal M. (Cardiology and Cardiovascular Medicine, 2022)
Since the availability of the vaccine against severe acute respiratory syndrome, coronavirus 2 (SARS-CoV-2), the etiologic agent for COVID-19, at least 67% of the US population has been vaccinated with at minimum one dose, and 58.2% of the U.S. population has received two doses. Here, we present the first report of a patient who developed new-onset atrial fibrillation (AF) after receiving a booster dose of the Moderna COVID-19 vaccine. The benefit of the COVID-19 vaccine certainly outweighs the risks of adverse cardiac effects; however, recipients with known cardiac risk factors should be appropriately advised. The mechanism by which the COVID-19 vaccine causes adverse cardiac effects is presently unknown and is likely complex and multifactorial. Prospective studies are needed urgently to understand the mechanism and pathophysiology of such serious adverse events.